Tunable properties of silver (Ag) substituted BaFe2O4 nanoparticles for photovoltaic (PV) applications - Irum Shahid Khan; Iftikhar Hussain Gul (Discover Nano)
Abstract In this work, Ba1-xAgxFe2O4 (x = 0.0, 0.2, 0.3, 0.5) nanoparticles have been prepared using the sol–gel auto-combustion method providing the pioneering investigation of substitution of silver into barium ferrite, that is often associated with magnetic applications. A broad inspection has been performed on structural, magneto-electric, dielectric, and optical properties uncovering potential of Ag incorporated barium ferrite nano particles using X-ray diffraction, Vibrating sample magnetometer, Multiferroic system, Impedance Analyzer, UV visible diffuse reflectance spectroscopy, Fluorescence spectrophotometer and Photoluminescence (PL) system. The chemical bonding and functional groups of all samples were explored by Fourier transform infrared spectrometer as well as with RAMAN spectroscopy. The slight turn in orthorhombic structure from (Pnma 62) to (Bb21m 36) was detected from pure BaFe2O4 particles to Ag concentrated samples and also illustrated in 3D visualization. The formation of spherical nanoparticles (46-32 nm) with designed composition (Ba0.8Ag0.2Fe2O4, Ba0.7Ag0.3Fe2O4, Ba0.5Ag0.5Fe2O4) which was confirmed by Scanning electron microscopy and Energy dispersive x-ray spectroscopy separately. The maximum magnetization value of 22.3 emu/g was revealed by the Ba0.5Ag0.5Fe2O4 sample. The lowest energy band gap value of 1.5–1.8 eV was achieved by pristine and Ba0.7Ag0.3Fe2O4 making it eligible to operate within the ideal region of solar cell efficiency with reduced recombination losses. The PL emission intensity was also observed in the visible spectrum at 573–576 nm for Ag concentrated samples suggesting that material can efficiently absorb and release light in the solar spectrum’s most useful region. Significant leakage current was indicated by the PE loop with high conductivity, indicating that the material has reduced resistance and enhanced charge transport. Simulating solar illumination was used to evaluate the photovoltaic performance of nanoparticles, producing response curves for photocurrent and dark current revealing the improved photo current with Ag infusion. The valuable results of Ag-infused barium ferrites for dielectric, optical, and photovoltaic capabilities offered a fresh concept for using magnetic nanoparticles modified by silver as an encouraging development in the PV applications. Graphical Abstract